Patients’ and caregivers’ experiences of familial and social support in resource-poor settings: A systematically constructed review and meta-synthesis - Yakubu Salifu; Emmanuel Ekpor; Jonathan Bayuo; Samuel Akyirem; Kennedy Nkhoma (Palliative Care and Social Practice)
Background: Familial and social support for patients with life-limiting conditions is crucial, especially in resource-poor settings. However, limited knowledge exists about patients’ and caregivers’ experiences within these informal networks in such contexts. Aims: This systematic review aimed to (i) synthesise the experiences of patients and caregivers regarding familial and social support in resource-poor settings, and (ii) understand the challenges they face in order to provide evidence for more compassionate, culturally congruent palliative care. Design: Systematic review and meta-synthesis registered on PROSPERO (CRD42023486219). Methods: We searched CINAHL, MEDLINE, PsycINFO, and Scopus using keywords such as “familial and social support” and “chronic debilitating conditions” in low- and middle-income countries. Only English-language qualitative studies exploring familial and social support were included. Thomas and Harden’s approach was used for data synthesis, and the Joanna Briggs Institute’s critical appraisal checklist was used to assess the studies’ quality. Results: We report our findings using the Enhancing Transparency in Reporting the Synthesis of Qualitative Research (ENTREQ) guidelines. Following screening, 39 studies were retained from 9157 search results. Five key themes emerged: (1) Bearing the weight of financial strain; (2) Psychosocial support as a “lifeline” for care; (3) Hands-on help and guidance; (4) Cultural and social obligations; and (5) Developing a “thick skin” and having faith as a coping mechanism. The findings show that caregiving in the context of life-limiting illnesses is influenced by financial burdens, emotional challenges, and cultural obligations, with caregivers depending on spiritual and social networks. However, resource availability is inconsistent, underscoring the need for tailored interventions. Conclusion: Culturally specific palliative care strategies are necessary to ease caregiver burdens, improve resource distribution, and support the well-being of patients and caregivers in resource-poor settings.